Nitrogen-carbon aggregate and method for producing the same, and sodium ion battery containing the same
By adopting nitrogen-carbon sets with a divided air hole structure in the cathode active substances of sodium ion batteries, using plasma discharge methods to mix nitrogen to form nitrogen doped carbon nanoparticles with mixed-layer structures, solving existing existing existing existing The lack of discharge capacity and initial Kuron efficiency of sodium ion batteries have achieved efficient sodium ion diffusion and storage.
Patent Information
- Application Number
- CN202010488635.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2020-06-02
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-06-02
AI Technical Summary
The cathode active substances of existing sodium ion batteries have poor performance in discharge capacity and initial Coulomb efficiency, making it difficult to meet the demand for high-performance energy storage in fields such as electric vehicles and electric ships.
A nitrogen-carbon aggregate with a layered pore structure is used, and nitrogen is doped into the carbon precursor through a plasma discharge method to form nitrogen-doped carbon nanoparticles with a mixed layer structure of micropores, and through these nanoparticles The condensation forms an aggregate of medium-large hierarchical pore structure, thereby increasing active sites to improve the diffusion and storage capacity of sodium ions.
With the case without using a separate additive, a nitrogen-carbon collection of layered gas-pore structure with middle and large pores is formed, which improves the diffusion path and active site of sodium ions, significantly improved the discharge of sodium ion batteries Capacity and initial Kuron efficiency.
Smart Images

Figure CN113471429B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a nitrogen-carbon aggregate having a hierarchical pore structure, a nitrogen-carbon aggregate manufactured by the method, and a sodium ion battery comprising the nitrogen-carbon aggregate. Background Art
[0002] Recently, with the increasing demand for environmentally friendly vehicles, the electric vehicle market has shown a good development trend. As the energy storage medium for the above-mentioned electric vehicles, the most commonly used is lithium-ion batteries, but because the amount of lithium buried on the earth is limited to very few countries, it is difficult to meet its market demand. Therefore, it is impossible to quickly meet the growing market demand for electric vehicles. In addition, according to the announcement of the International Maritime Organization, strict greenhouse gas emission reduction regulations will be implemented from 2003. In order to meet the values required in the above-mentioned greenhouse gas emission rules, in addition to electric vehicles, electric ships will inevitably become a future development trend.
[0003] Therefore, the demand for lithium-ion batteries will also increase significantly in the future, but it will be difficult to maintain the price of lithium-ion batteries stably when the demand for lithium-ion batteries increases sharply. In addition, in the past, the demand field centered on mobile devices simply required high reversible capacity characteristics, but in today's demand field centered on electric vehicles and electric ships, in addition to the above characteristics, high discharge rate performance is also required.
[0004] Therefore, various types of batteries are being studied as alternatives to lithium-ion batteries. Among them, sodium-ion batteries are attracting attention as a next-generation rechargeable battery that can replace lithium-ion batteries because sodium precursors are abundant in the earth's crust and seawater.
[0005] Because the sodium-ion battery as described above works based on an electrochemical reaction similar to that of a lithium-ion battery, graphite was first used as the cathode active material. However, because of the thermodynamic instability between sodium ions and graphite applicable to sodium-ion batteries, sodium-graphite intercalation compounds (Na-GIC) cannot be formed, so its reversible capacity can only reach 1 / 10 of that of lithium-ion batteries. For this reason, hard carbon with a large number of nanopores and nanovoids is being studied as an alternative to graphite, but hard carbon still only exhibits a relatively low reversible capacity performance that is difficult to achieve practical application. Moreover, the initial coulombic efficiency of the above-mentioned hard carbon is mostly below 50%, so it is difficult to achieve commercialization.
[0006] As a related prior art, a patent using hard carbon as a cathode active material is disclosed in "Sodium Ion Secondary Battery (Registration No.: 10-1635850)". However, in the above patent, sodium exhibits slow kinetic characteristics due to the randomly arranged graphene sheet structure in the hard carbon, making it difficult to meet the higher discharge capacity (rate-capability) requirements.
[0007] Therefore, there is an urgent need to research and develop a new technology that can produce a cathode active material that has a stable life while satisfying excellent discharge capacity and high initial coulombic efficiency and apply it to sodium ion batteries.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Korean Domestic Registered Patent Gazette No. 10-1635850, registered on June 28, 2016 Summary of the invention
[0011] Problems to be solved by the invention
[0012] The technical problem to be solved by the present invention is to provide a method for manufacturing a nitrogen-carbon aggregate with a hierarchical pore structure that can increase active sites for adsorbing and storing sodium ions by nitrogen doping in order to meet the above-mentioned technical development requirements.
[0013] In addition, the technical problem to be solved by the present invention is to provide a nitrogen-carbon aggregate produced by the above method.
[0014] In addition, the technical problem to be solved by the present invention is to provide a sodium ion battery including the above-mentioned nitrogen-carbon assembly.
[0015] Solutions for solving problems
[0016] In order to solve the technical problems mentioned above, the present invention provides a method for manufacturing a nitrogen-carbon aggregate with a hierarchical pore structure, characterized in that it includes: a first step of manufacturing a precursor solution containing a nitrogen-containing carbon precursor; a second step of configuring a pair of metal wires to the above-mentioned precursor solution; and a third step of performing plasma discharge by loading power to the above-mentioned metal wires, thereby forming nitrogen-doped carbon nanoparticles with a mixed-layer structure having micropores on the surface while the carbon and nitrogen of the above-mentioned carbon precursor are combined, and an aggregate with a medium-large hierarchical pore structure is formed by the agglomeration of the above-mentioned carbon nanoparticles; wherein the active site of the above-mentioned aggregate is increased by the above-mentioned nitrogen doping.
[0017] The present invention is characterized in that the nitrogen-containing carbon precursor is a heterocyclic amine having a nitrogen atom.
[0018] The present invention is characterized in that the above-mentioned heterocyclic amine is one or more selected from the group consisting of pyridine, quinoline, isoquinoline, pyrrole, pyrrolidine, piperidine, indole, imidazole, pyrimidine and melamine.
[0019] The present invention is characterized in that the Brunauer-Emmett-Teller (BET) specific surface area of the carbon nanoparticles is 200 to 400 m 2 / g.
[0020] In order to solve the other technical problem as described above, the present invention provides a nitrogen-carbon aggregate characterized by being manufactured using the above-mentioned manufacturing method.
[0021] In order to solve another technical problem as described above, the present invention provides a sodium ion battery, characterized in that it includes: an electrode containing the above-mentioned nitrogen-carbon aggregate; and an electrolyte that accommodates the above-mentioned electrode and uses sodium ions as a transfer medium.
[0022] Effects of the Invention
[0023] The following effects can be achieved by the method for producing a nitrogen-carbon aggregate having a hierarchical pore structure as described above, the nitrogen-carbon aggregate produced by the method, and the sodium ion battery including the nitrogen-carbon aggregate.
[0024] First, without using a separate additive, nitrogen-doped carbon nanoparticles with micropores on the surface can be formed by plasma discharge using only a nitrogen-containing carbon precursor solution, and a nitrogen-carbon aggregate with a hierarchical pore structure of mesopores and macropores can be produced through the agglomeration of the above nitrogen-doped carbon nanoparticles.
[0025] Second, by forming the nitrogen-doped carbon nanoparticles constituting the nitrogen-carbon aggregate in nanometer-level size, the diffusion path of the sodium ions is shortened and a wide path is formed through the mixed layer structure inside the nanoparticles, thereby ensuring sufficient cavities.
[0026] Third, by increasing the active sites of the nitrogen-carbon aggregate by means of non-intrinsic defects generated on the carbon nanoparticles through nitrogen doping, sufficient contact force is provided at the interface between the electrode and the electrolyte when it is applied to the cathode active material of the sodium ion battery and the internal diffusion of sodium ions becomes easier, thereby having an excellent discharge capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a sequence diagram illustrating the steps of the method for producing a nitrogen-carbon aggregate to which the present invention is applied.
[0028] Figure 2 This is a schematic diagram illustrating plasma discharge performed to produce a nitrogen-carbon aggregate according to the present invention.
[0029] Figure 3 This is a schematic diagram illustrating the nitrogen-carbon aggregate produced according to the present invention.
[0030] Figure 4 This is a diagram illustrating a nitrogen-carbon aggregate to which the present invention is applicable.
[0031] Figure 5 (a) is a graph showing the nitrogen adsorption-desorption isotherms of nitrogen-doped carbon nanoparticles using pyridine, Figure 5 (b) is a graph illustrating the pore size distribution of nitrogen-doped carbon nanoparticles using pyridine.
[0032] Figure 6 (a) is a graph showing the nitrogen adsorption-desorption isotherms of nitrogen-doped carbon nanoparticles using pyrrole, Figure 6 (b) is a graph illustrating the pore size distribution of nitrogen-doped carbon nanoparticles using pyrrole.
[0033] Figure 7 (a) is a graph showing the nitrogen adsorption and desorption isotherms of carbon black using benzene. Figure 7 (b) is a graph illustrating the pore size distribution of carbon black using benzene.
[0034] Figure 8 (a) is a graph illustrating an X-ray photoelectron spectroscopy (XPS) spectrum of nitrogen-doped carbon nanoparticles. Figure 8 (b) is a graph illustrating a high-resolution X-ray photoelectron spectroscopy (HR-XPS) spectrum of N1 of nitrogen-doped carbon nanoparticles.
[0035] Fig. 9 (a) is a graph illustrating cyclic voltammetry (CV) curves of the first three cycles at a scan rate of 0.2 mV / s and a potential range of 0.01 to 3.0 V, Fig. 9 (b) is a graph illustrating an initial charge and discharge characteristic curve of the nitrogen-carbon aggregate at a current density of 1 A / g.
[0036] Fig.10 (a) is a graph illustrating cyclic voltammetry (CV) curves from 0.01 to 3.0 V at different scan rates, Fig.10 (b) is a graph illustrating the linear relationship between the logarithm of the peak current and the logarithm of the scan rate. Fig.10 (c) is a graph illustrating the capacity contribution ratio relative to the total capacity based on the scan rate, Fig.10 (d) is a graph illustrating the relationship between the cyclic voltammetry (CV) curve and the capacity contribution at a scan rate of 0.7 mV / s.
[0037] Fig.11 (a) is a graph showing the speed performance based on the current density. Fig.11 (b) is a graph showing a comparison of the speed performance between conventional nitrogen-doped carbon and nitrogen-doped carbon nanoparticles applicable to the present invention. Fig.11 (c) is a graph illustrating the cycle performance at a current density of 100 mAh / g. DETAILED DESCRIPTION
[0038] Next, the present invention will be described in detail.
[0039] It should be noted that the macropores described in this specification refer to pores with an average diameter exceeding 50 nm, the mesopores refer to pores with an average diameter of 2 nm to 50 nm, and the micropores refer to pores with an average diameter of less than 2 nm.
[0040] In addition, the turbostratic structure described in this specification refers to a structure in which the crystal regions have no regularity and exhibit a certain degree of random orientation in three dimensions.
[0041] In addition, the extrinsic defect described in this specification refers to a crystalline region that cannot form a complete crystal lattice by atomic doping.
[0042] In addition, the active site described in this specification refers to a space where atomic ions are adsorbed when applied to a cathode active material of a battery.
[0043] In one aspect, the present invention relates to a method for manufacturing a nitrogen-carbon aggregate having a hierarchical pore structure. Figure 1This is a sequence diagram illustrating the process of the method for producing the nitrogen-carbon aggregate applicable to the present invention. Figure 1 As shown, the method for manufacturing a nitrogen-carbon aggregate applicable to the present invention comprises: a first step S10, manufacturing a precursor solution containing a nitrogen-containing carbon precursor; a second step S20, configuring a pair of metal wires for the precursor solution; and a third step S30, performing plasma discharge by applying power to the metal wires, thereby forming nitrogen-doped carbon nanoparticles having a mixed layer structure with micropores on the surface while combining carbon and nitrogen in the carbon precursor, and forming an aggregate having a medium-large layered pore structure by agglomeration of the carbon nanoparticles. In this way, a nitrogen-carbon aggregate can be manufactured that forms a wide path through the mixed layer structure inside the nitrogen-doped carbon nanoparticles and thereby ensures sufficient cavities, and increases the active sites of the nitrogen-carbon aggregate by means of non-intrinsic defects generated on the carbon nanoparticles by nitrogen doping.
[0044] In the method for producing a nitrogen-carbon aggregate to which the present invention is applied, the first step S10 is a step of producing a precursor solution containing a nitrogen-containing carbon precursor.
[0045] That is, a liquid carbon precursor containing nitrogen atoms is prepared, and the above solution will be used in the subsequent third step to perform carbon synthesis and nitrogen doping in situ to form nitrogen-doped carbon nanoparticles, and at the same time, a nitrogen-carbon aggregate formed by the agglomeration of nitrogen-doped carbon nanoparticles will be formed.
[0046] As the nitrogen-containing carbon precursor, a heterocyclic amine having a nitrogen atom is preferably used. A heterocyclic amine is a compound in which a nitrogen atom occupies a part of a ring, thereby enabling nitrogen to be doped into the carbon nanoparticles while synthesizing the carbon nanoparticles. The above heterocyclic amines can be divided into several types as described below according to the number of nitrogen atoms contained in the ring.
[0047] The heterocyclic amine containing one nitrogen atom may be one or more selected from the group consisting of pyridine, pyridine homologues, pyridine isomers, pyridine homologue isomers, quinoline, isoquinoline, acridine, pyrrole, pyrrolidine, piperidine and indole. The heterocyclic amine containing two nitrogen atoms may be one or more selected from the group consisting of imidazole and pyrimidine. The heterocyclic amine containing three nitrogen atoms may be melamine.
[0048] It should be noted that the heterocyclic amine is not limited to the above-mentioned types, and any heterocyclic amine can be used as long as it contains 1 to 3 nitrogen atoms in the ring. In some cases, when a solid heterocyclic amine is used, it can be dissolved in a liquid heterocyclic amine for use.
[0049] Next, the second step S20 is a step of configuring a pair of metal wires for the precursor solution.
[0050] like Figure 2 As shown, in order to form nitrogen-doped carbon nanoparticles and nitrogen-carbon aggregates by solution plasma process (SPP), electrodes are prepared for configuration in a chamber, namely a pair of tungsten carbides and a ceramic tube wrapped around the tungsten carbide to protect it, and a power supply unit (not shown) for loading power to the electrodes.
[0051] That is, the chamber forms a space for accommodating the carbon precursor therein and provides a space for liquid phase plasma discharge. In order to form nitrogen-doped carbon nanoparticles and nitrogen-carbon aggregates by inducing plasma discharge in the solution, the electrodes are arranged in a row in the chamber in a manner facing each other along the length direction. It should be noted that the electrode will be interpreted in the same meaning as the metal wire.
[0052] Finally, the third step S30 is a step of performing plasma discharge by loading power to the metal wire, thereby forming nitrogen-doped carbon nanoparticles with a mixed-layer structure having micropores on the surface while combining the carbon and nitrogen in the carbon precursor, and forming an aggregate with a medium-large layered pore structure through the agglomeration of the carbon nanoparticles.
[0053] The aggregate refers to a nitrogen-carbon aggregate formed by agglomeration of nitrogen-doped carbon nanoparticles having micropores on the surface formed when carbon and nitrogen are combined. The nitrogen-carbon aggregate produced according to the present invention can be illustrated by a schematic diagram, that is, Figure 3 to confirm.
[0054] In order to achieve the movement and diffusion of sodium ions, the pore structure is particularly important, such as Figure 3 The nitrogen-carbon aggregate shown in FIG. 1 also has a mixed layer structure in addition to macropores, mesopores and micropores, which can be formed by Figure 2 The plasma discharge shown was used for synthesis.
[0055] The plasma discharge is performed by applying a bipolar pulsed direct current power supply with a pulse width of 0.1 to 3 μs, a frequency of 80 to 150 kHz, and a voltage of 1.0 to 5.0 kV.
[0056] When the pulse width is less than 0.1 μs, insufficient nitrogen doping into carbon nanoparticles may occur, while when it exceeds 3 μs, excessive reaction between carbon synthesis and nitrogen doping may hinder the increase of active sites. Therefore, the pulse width is preferably 0.1 to 3 μs, and particularly preferably 1 μs.
[0057] When the frequency is less than 80 kHz, the plasma may be shut down, and when it exceeds 150 kHz, it may cause problems in transitioning to arc plasma. Therefore, the frequency is preferably in the range of 80 to 150 kHz, especially 100 kHz.
[0058] When the voltage is less than 1.0 kV, the plasma may be shut down during the plasma discharge due to insufficient voltage, and when it exceeds 5.0 kV, it is difficult to form nitrogen-doped carbon nanoparticles because the plasma transitions to arc plasma, and the agglomeration of nitrogen-doped carbon nanoparticles cannot be achieved. Therefore, the voltage is preferably 1.0 to 5.0 kV, especially 1.2 kV.
[0059] Through the plasma discharge as described above, the nitrogen-containing carbon precursor solution will form nitrogen-doped carbon nanoparticles with a size of 20 to 40 nm and form a morphology with a hierarchical pore structure by mutual agglomeration.
[0060] When the size of nitrogen-doped carbon nanoparticles is less than 20nm, it will be difficult to form a sufficient medium-large layered pore structure. When the size of nitrogen-doped carbon nanoparticles exceeds 40nm, the diffusion of sodium ions will be hindered due to insufficient space between the mixed layer structures, or the problem of inducing breakage of nitrogen-doped carbon nanoparticles due to excessive spacing between the mixed layer structures will occur. Therefore, it is advisable to form nitrogen-doped carbon nanoparticles with a size of 20 to 40nm to form a shorter sodium ion diffusion path inside the nitrogen-carbon aggregate and thereby achieve rapid internal diffusion.
[0061] At this time, the Brunauer-Emmett-Teller (BET) specific surface area of the nitrogen-doped carbon nanoparticles can be 200 to 400 m 2 / g. When the Brunauer-Emmett-Teller (BET) specific surface area of nitrogen-doped carbon nanoparticles is less than 200 m 2 / g, the movement of sodium ions is hindered because sufficient contact force cannot be provided at the interface between the electrode and the electrolyte. In contrast, when the Brunauer-Emmett-Teller (BET) specific surface area of nitrogen-doped carbon nanoparticles exceeds 400 m 2 / g, although sufficient contact can be achieved at the interface between the electrode and the electrolyte, the Brunauer-Emmett-Teller (BET) specific surface area is too large, which will induce side reactions and cause a sharp drop in the initial coulomb efficiency, thereby reducing the life span. Therefore, the Brunauer-Emmett-Teller (BET) specific surface area of nitrogen-doped carbon nanoparticles is 200 to 400 m 2 It should be noted that the Brunauer-Emmett-Taylor (BET) specific surface area is obtained by analyzing the adsorption amount data compared with the relative pressure based on the argon adsorption method (argon isothermal adsorption-desorption curve) using the Brunauer-Emmett-Taylor (BET) equation.
[0062] In particular, the mixed layer structure of nitrogen-doped carbon nanoparticles is composed of multiple crystalline domains, which form wide paths to form cavities, thus facilitating the diffusion of sodium ions. In addition, when nitrogen is doped into carbon nanoparticles, 10 to 20 nanometers of pores are formed on the crystalline domains due to non-intrinsic defects caused by nitrogen atoms. The large space increases the active sites of the nitrogen-carbon aggregate, making the diffusion of sodium ions easier.
[0063] Therefore, through the third step, it is possible to produce nitrogen-doped carbon nanoparticles having a wider specific surface area so that sodium ions moving to the interface between the electrode and the electrolyte can easily enter the interior of the cathode active material and having micropores on the surface that allow sodium ions to undergo a co-intercalation reaction with the ether-based electrolyte, as well as a nitrogen-carbon aggregate with a hierarchical pore structure that allows sodium ions in the electrolyte to quickly move to the electrode interface.
[0064] That is, by forming nano-sized nitrogen-doped carbon nanoparticles, sodium ions inserted into the cathode active material can diffuse in the shortest distance and increase active sites by extrinsic defects induced by doped nitrogen, thereby producing a nitrogen-carbon aggregate with high discharge capacity.
[0065] In the nitrogen-carbon aggregate as described above, nitrogen-doped carbon nanoparticles with a three-dimensional network structure are formed by interconnecting micropores, mesopores and macropores in three dimensions, wherein the micropores enable sodium ions to undergo a co-intercalation reaction with the ether-based electrolyte and form a transport path for sodium ions, while the macropores can act as an ion buffer to shorten the diffusion distance of sodium ions and thereby achieve the effect of improving the electrochemical properties.
[0066] Through the manufacturing method as described above, the present invention can configure a pair of metal wires in a precursor solution containing a nitrogen-containing carbon precursor and then load power to the metal wires for plasma discharge so that nitrogen is combined with carbon to form nitrogen-doped carbon nanoparticles with a mixed-layer structure having micropores. At the same time, the present invention can form an aggregate with a medium-large layered pore structure through the agglomeration of the above-mentioned carbon nanoparticles, thereby increasing the active sites of the aggregate through nitrogen doping.
[0067] In particular, the nitrogen-carbon aggregate is a carbon black form formed by agglomeration of nitrogen-doped carbon nanoparticles of 20 to 40 nm in size, and has a hierarchical pore structure of mesopores and macropores. Thus, the nitrogen-doped carbon nanoparticles can not only shorten the diffusion path of sodium ions, but also form a wide path through the mixed layer structure inside the nitrogen-doped carbon nanoparticles, thereby making the diffusion of sodium ions easier. In addition, the active sites of the nitrogen-carbon aggregate can be increased through the wider comparative area of the nitrogen-doped carbon nanoparticles and the non-intrinsic defects formed by nitrogen doping, thereby making the diffusion of sodium ions easier and achieving excellent discharge capacity.
[0068] On the other hand, the present invention relates to a nitrogen-carbon aggregate having a hierarchical pore structure, which can be manufactured by the manufacturing method described above. That is, the present invention relates to an aggregate having a medium-large hierarchical pore structure formed by agglomeration of the carbon nanoparticles by plasma discharge in a precursor solution containing a nitrogen-containing carbon precursor so that nitrogen is incorporated into carbon to form nitrogen-doped carbon nanoparticles having a mixed-layer structure with micropores, characterized in that active sites are increased by nitrogen doping.
[0069] The above-mentioned nitrogen-carbon aggregate is formed into a three-dimensional network morphology by the agglomeration of nitrogen-doped carbon nanoparticles, and micropores are formed on the surface of the nitrogen-doped carbon nanoparticles while forming a layered pore structure composed of a plurality of macropores with an average pore diameter exceeding 50 nm and a plurality of mesopores with an average pore diameter of 2 nm to 50 nm located adjacent to the macropores.
[0070] That is, the nitrogen-carbon aggregate forms a carbon black morphology by interconnecting macropores, mesopores and micropores in three dimensions, and in particular, the nitrogen-doped carbon nanoparticles constituting the nitrogen-carbon aggregate are formed by a plurality of 10 to 10 nanometers. A mixed layer structure consisting of crystalline regions of different sizes.
[0071] In this regard, Figure 4 , a diagram of a nitrogen-carbon aggregate to which the present invention is applied is shown, and it can be confirmed that nitrogen-doped carbon nanoparticles composed of spherical forms are aggregated to form a hierarchical pore structure of the nitrogen-carbon aggregate.
[0072] See the diagram of nitrogen-carbon aggregates using transmission electron microscopy (TEM, JEM-2100F) Figure 4 (a) Figure 4 (b) and Figure 4 (c) can confirm that nitrogen-doped carbon nanoparticles with uniform spherical morphology and a diameter of about 20 to 40 nm are formed, and each nitrogen-doped carbon nanoparticle is not in the form of plate-like graphene, but in the form of carbon black that is interconnected in a chain-like agglomeration state through diffusion limited aggregation (DLA).
[0073] In addition, it can be confirmed that a medium-large hierarchical pore structure is formed by forming mesopores and macropores between the condensed carbon nanoparticles. The hierarchical pore structure as described above can easily move sodium ions from the bulk area of the electrolyte to the surface of the nitrogen-doped carbon nanoparticles, thereby maximizing the discharge capacity of the sodium ion battery.
[0074] exist Figure 4 In (d), a high-resolution transmission electron microscope (HR-TEM, JEM-2100F) of nitrogen-doped carbon nanoparticles is shown, which confirms that a mixed layer structure with a relatively low annealing temperature is formed inside. Through the mixed layer structure as described above, a large number of voids can be formed to promote the adsorption and storage capacity of sodium ions.
[0075] also, Figure 4 (e) is the result of elemental mapping using X-ray energy dispersive spectroscopy (EDS) installed in a transmission electron microscope (TEM) device in order to investigate the nitrogen distribution in the synthesized nitrogen-doped carbon nanoparticles, as shown in FIG. Figure 4 As shown in (e), it can be confirmed that nitrogen is uniformly distributed in the carbon nanoparticles.
[0076] On the other hand, the present invention relates to a sodium ion battery comprising a nitrogen-carbon aggregate having a hierarchical pore structure, characterized in that it includes: an anode; a cathode, comprising a current collector coated with a nitrogen-carbon aggregate having a hierarchical pore structure; and an ether-based electrolyte.
[0077] A sodium ion battery comprises: an anode containing an anode active material for storing sodium ions during discharge; a cathode containing a cathode active material for storing sodium ions during charge; a separation membrane for transferring sodium ions between the anode and the cathode; and an electrolyte for transferring sodium ions between the anode and the cathode.
[0078] Preferably, the cathode, the anode and the separation membrane together constitute an electrode assembly, and the electrode assembly and the electrolyte are housed in a housing to form a sodium ion battery. The cathode is composed of a current collector and a slurry coated on the surface of the current collector, and the slurry can be a mixture of the nitrogen-carbon assembly applicable to the present invention and a conductive material, a polymer and other additives.
[0079] For reference, as the current collector, copper foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, or a combination thereof can be used.
[0080] Next, the embodiments applicable to the present invention will be described in more detail. It should be noted that the following embodiments are only exemplary contents provided to help understand the present invention, and the scope of the present invention is not limited thereby.
[0081] <Example 1> Production of nitrogen-carbon aggregate using pyridine
[0082] A nitrogen-carbon aggregate was synthesized by using a pyridine solution as a precursor solution containing a nitrogen-containing carbon precursor and performing plasma discharge at room temperature and atmospheric conditions for 20 minutes (see Figure 2 as well as Figure 3 ).
[0083] At this time, the pulse width was set to 1 μs and the frequency was set to 100 kHz, and then a 1.2 kV bipolar high voltage pulse was generated using a PeKuris MPP-HV04 high voltage bipolar pulse generator and applied to a pair of tungsten carbide electrodes.
[0084] The synthesized nitrogen-carbon aggregate was separated into particles using filter paper and then dried at 90°C for 12 hours. The dried particles were then uniformly ground and heat treated at 500°C for 3 hours in a quartz tube furnace in a nitrogen atmosphere at a heating rate of 10°C / min.
[0085] <Example 2> Production of nitrogen-carbon aggregate using pyrrole
[0086] A pyrrole solution was used as a precursor solution containing a nitrogen-containing carbon precursor and plasma discharge was performed at room temperature and in the atmosphere for 20 minutes, thereby synthesizing a nitrogen-carbon aggregate.
[0087] At this time, the pulse width was set to 1 μs and the frequency was set to 100 kHz, and then a 1.2 kV bipolar high voltage pulse was generated using a PeKuris MPP-HV04 high voltage bipolar pulse generator and applied to a pair of tungsten carbide electrodes.
[0088] The synthesized nitrogen-carbon aggregate was separated into particles using filter paper and then dried at 90°C for 12 hours. The dried particles were then uniformly ground and heat treated at 500°C for 3 hours in a quartz tube furnace in a nitrogen atmosphere at a heating rate of 10°C / min.
[0089] <Comparative Example 1> Production of Carbon Black Using Benzene
[0090] Carbon black was synthesized by using a benzene solution as a precursor solution containing a nitrogen-free carbon precursor and performing plasma discharge at room temperature and atmospheric conditions for 20 minutes.
[0091] At this time, the pulse width was set to 1 μs and the frequency was set to 100 kHz, and then a 1.2 kV bipolar high voltage pulse was generated using a PeKuris MPP-HV04 high voltage bipolar pulse generator and applied to a pair of tungsten carbide electrodes.
[0092] The synthesized carbon black was separated into particles using filter paper and then dried at 90°C for 12 hours. The dried particles were then uniformly ground and heat treated at 500°C for 3 hours in a quartz tube furnace in a nitrogen atmosphere at a heating rate of 10°C / min.
[0093] The nitrogen adsorption / desorption isotherms and pore distribution of the nitrogen-carbon aggregates prepared in Examples 1 and 2 and the carbon black prepared in Comparative Example 1 were measured, and the results were as follows: Figures 5 to 7 shown.
[0094] It should be noted that the nitrogen adsorption-desorption isotherms were measured at 77 K using a N2 adsorption analyzer (MicrotracBEL Corp., Belsorp-max), and each sample was degassed at 300°C for 2 hours before the measurement. The specific surface area was calculated using the Brunauer-Emmett-Teller (BET) method, and the pore distribution was obtained from the adsorption isotherm curve using the Barrett-Joyner-Halenda (BJH) method.
[0095] Figure 5 (a) is a graph showing the nitrogen adsorption-desorption isotherms of nitrogen-doped carbon nanoparticles using pyridine. Figure 5 (a) The pore structure of nitrogen-doped carbon nanoparticles can be confirmed by nitrogen adsorption-desorption isotherms. Figure 5 The adsorption curve in (a) shows the hysteresis loop indicating the existence of mesopores and a continuous pore distribution is formed in the range of 10 to 150 nm. For reference, the total pore volume of nitrogen-doped carbon nanoparticles is 1.2975 cm 3 / g, and the mesopore volume is 0.6057cm 3 / g, and the macropore volume is 0.6659 cm 3 / g, and the average pore diameter is 15.77nm.
[0096] Figure 5 (b) is a graph showing the micropore size distribution of nitrogen-doped carbon nanoparticles using pyridine. Figure 5 (b), it can be confirmed that there are extrinsic defects and micropores of nitrogen-doped carbon nanoparticles in a narrow distribution of 0.5 to 0.8 nm.
[0097] In addition, the specific surface area of nitrogen-doped carbon nanoparticles calculated by the Brunauer-Emmett-Teller (BET) method was 265.15 m 2 / g, it can be confirmed that the larger specific surface area of nitrogen-doped carbon nanoparticles can provide sufficient contact force for the accumulation of sodium ions or charges at the interface between the electrode and the electrolyte. As mentioned above, the larger specific surface area of carbon nanoparticles can increase the area of the electrolyte in contact with the electrode, thereby increasing the interface contact of sodium ions.
[0098] This confirms that the wider specific surface area of the carbon nanoparticles can increase the accessibility of sodium ions, and that sodium ions can easily enter and exit in a solvated state through the micropores formed on the surface of the carbon nanoparticles.
[0099] Figure 6 (a) is a graph showing the nitrogen adsorption-desorption isotherms of nitrogen-doped carbon nanoparticles using pyrrole. Figure 6 (a) The pore structure of nitrogen-doped carbon nanoparticles can be confirmed by nitrogen adsorption-desorption isotherms. Figure 5 Similar to (a), the hysteresis loop indicating the existence of mesopores can be confirmed from the adsorption curve and a continuous pore distribution is formed in the range of 10 to 150 nm.
[0100] Figure 6 (b) is a graph illustrating the micropore size distribution of nitrogen-doped carbon nanoparticles using pyrrole. Figure 5 Similar to (b), it can be confirmed that there are extrinsic defects and micropores of nitrogen-doped carbon nanoparticles in a narrow distribution of 0.5 to 0.8 nm.
[0101] In addition, the specific surface area of nitrogen-doped carbon nanoparticles calculated by the Brunauer-Emmett-Teller (BET) method was 260.84 m2 / g, which is similar to the specific surface area of Example 1. It can be confirmed that by providing sufficient contact force for the accumulation of sodium ions or charges at the interface between the electrode and the electrolyte, the area of the electrolyte in contact with the electrode can be increased, thereby increasing the interfacial contact of the sodium ions.
[0102] Figure 7 (a) is a graph showing the nitrogen adsorption and desorption isotherms of carbon black using benzene, and Figure 5 (a) and Figure 6 Different from (a), it can be confirmed that the pore distribution presents different states in the range of 10 to 150 nm.
[0103] Figure 7 (b) is a graph showing the pore size distribution of carbon black using benzene. Figure 7 (b) can confirm that there is no Figure 5 (b) and Figure 6 (b) Similar extrinsic defects as well as microvoids exist.
[0104] In addition, the specific surface area of carbon black calculated by the Brunauer-Emmett-Teller (BET) method is 243.15 m 2 / g, which is relatively smaller than the specific surface area of Examples 1 and 2. It can be confirmed that this is not conducive to the movement of sodium ions because sufficient contact force cannot be provided at the interface between the electrode and the electrolyte.
[0105] That is, by the comparative example 1 Figure 7 It can be confirmed that although some mesopores and macropores of the hierarchical pore structure can be observed in the carbon black produced by plasma discharge using benzene solution, uniform micropores cannot be formed. Figure 5 as well as Figure 6 It was confirmed that in the nitrogen-carbon aggregate produced by plasma discharge using a pyridine solution or a Biluo solution, a hierarchical pore structure of mesopores and macropores and micropores formed on the surface of nitrogen-doped carbon nanoparticles were observed.
[0106] <Test Example 1>
[0107] In this test example, the electrochemical properties of nitrogen-carbon aggregates containing nitrogen-doped carbon nanoparticles were tested. The electrochemical properties test was performed using coin-type half-cells (CR2032, Wellcoscorp.). The galvanostatic charge-discharge test was performed using a BCS-805 Biologic battery test system in a voltage range of 0.01 to 3.0 V (vs. Na / Na+). The cyclic voltammetry (CV) test was performed using the same method, and the electrochemical impedance spectroscopy (EIS) test was also performed using the same device in a frequency range of 100 kHz to 0.01 Hz.
[0108] Preparation of battery samples
[0109] As a working electrode, 70 wt% of an active material consisting of a nitrogen-carbon aggregate applicable to the present invention, 10 wt% of conductive carbon black, and 20% of polyacrylic acid were mixed and dissolved in distilled water to produce a slurry. The slurry produced by the above method was evenly applied to a copper foil using a doctor blade and dried in a vacuum drying oven at 80°C for 12 hours. Next, after being squeezed to a thickness of 35 μm using a roller press, it was punched into a coin type using a punching tool. The weight of the sample was measured 3 to 4 times using an electronic analytical balance, and the result was about 1.8 mg / cm.
[0110] A coin cell was assembled in an Ar-filled glove box using the metal as the counter electrode, a glass fiber filter as the separation membrane, and a 1 M NaPF6 diethylene glycol dimethyl ether (DEGDME) solution as the electrolyte.
[0111] Elemental analysis
[0112] In order to investigate the surface composition and bonding state of nitrogen-doped carbon nanoparticles, X-ray photoelectron spectroscopy (XPS) and high-resolution X-ray photoelectron spectroscopy (HR-XPS) were measured. The results are as follows: Figure 8 (a) and Figure 8 as shown in (b).
[0113] Figure 8 (a) is a graph showing an X-ray photoelectron spectroscopy (XPS) spectrum of nitrogen-doped carbon nanoparticles to which the present invention is applied. Figure 8 In (a), peaks consistent with C1, N1 and O1 appear, among which C1 is 93.9at%, N1 is 2.6at% and O1 is 3.5at%.
[0114] Because plasma discharge generates plasma in a nitrogen-containing precursor solution, it can completely isolate external oxygen. That is, because there is no oxygen in the nitrogen-containing carbon precursor solution, the possibility of nitrogen being oxidized can be eliminated from the source. Figure 8 The O1 peak measured in (a) is the oxygen adsorbed on the surface during sample preparation and measurement.
[0115] Figure 8 (b) is a graph illustrating a high-resolution X-ray photoelectron spectroscopy (HR-XPS) spectrum of N1 of the nitrogen-doped carbon nanoparticles of the present invention. Figure 8 As shown in (b), N1 exhibits peaks representing N-6 (pyridinic-N), N-5 (pyrrolic-N) and NQ (graphitic) at 398.7, 400.2 and 401.2 eV, respectively.
[0116] In particular, through Figure 8 (b) confirms that nitrogen is doped into the carbon nanoparticles. Among the total nitrogen dopants, N-6 and N-5 account for a relatively high proportion of 50.6% and 30.0%, respectively, which plays an important role in determining the reversible capacity. It can be seen that the nitrogen atoms are present in the non-intrinsic defect part or the edge part rather than the surface of graphene. N-6 and N-5 can be incorporated into the lattice of the non-intrinsic defect or edge part of the carbon nanoparticles, thereby increasing the active sites that help the diffusion of sodium ions and thereby increasing the movement and storage capacity of sodium ions. In addition, NQ and the micropores formed on the surface of carbon nanoparticles can improve their conductivity by inducing the co-embedding reaction of sodium ions and ether-based electrolytes.
[0117] With Figure 8 Unlike the nitrogen-doped carbon nanoparticles shown, for carbon black synthesized using a nitrogen-free carbon precursor, since no nitrogen is doped into the carbon black, no empty space can be formed in the carbon lattice constituting the carbon black, and thus no active sites that can help sodium ions diffuse easily can be formed.
[0118] Charge and discharge characteristics analysis
[0119] Fig. 9(a) is a graph illustrating cyclic voltammetry (CV) curves of the initial three cycles at a scan rate of 0.2 mV / s and a potential range of 0.01 to 3.0 V.
[0120] During the reduction process, there was no clear peak representing electrolyte decomposition between the first (1st) cycle and the second (2nd) cycle, indicating that some sodium ions were captured without forming a solid-electrolyte interphase (SEI) film. By overlapping the second (2nd) cycle with the third (3rd) cycle, it was confirmed that the insertion and removal and adsorption and desorption reactions of sodium ions can be stably achieved.
[0121] exist Fig. 9 The pair of sharp redox peaks in the low potential region (0.01 to 0.15 V) of the cyclic voltammetry (CV) curve of (a) are derived from the co-insertion and extraction reactions of sodium ions and ether solvents and molecular reactions within the graphite structure. The broader peaks from 0.14 to 3.0 V are derived from the adsorption and desorption reactions on small graphite clusters.
[0122] Fig. 9 (b) is a graph illustrating the initial charge-discharge characteristic curve at a current of 1 A / g. Although the specific surface area is large (328.93 m 2 / g), but its initial coulombic efficiency is only 80%. This is consistent with the results of the cyclic voltammetry (CV) curve mentioned above, indicating that there is no direct relationship between the specific surface area and the initial coulombic efficiency.
[0123] The discharge characteristic curve can be divided into a small plateau region less than 0.15 V and a slope region above 0.15 V, which is consistent with the cyclic voltammetry (CV) results mentioned above. The capacities of the plateau region and the slope region are 23 mAh / g and 264 mAh / g, respectively, indicating that adsorption and desorption dominate the storage of sodium ions.
[0124] Analysis of the storage capacity of sodium ions
[0125] first, Fig.10 (a) is a graph illustrating cyclic voltammetry (CV) curves from 0.01 to 3.0 V at different scan rates. Fig.10 (a), the adsorption-desorption reaction can be calculated by the following description formula 1.
[0126] [Formula 1]
[0127] I=av b
[0128] After calculating the b value from the cyclic voltammetry (CV) curves at different scan rates, the b value can be used to show the kinetic characteristics of sodium ion storage. When the b value is close to 0.5, it indicates that diffusion is dominant, while when it is close to 1, it can be inferred that it is a capacity-controlled reaction.
[0129] Fig.10 (b) is a graph illustrating the linear relationship between the logarithm of the peak current and the logarithm of the scanning speed. Fig.10 As shown in (b), the b value is 0.7615 and 0.8425, which are close to 1, which confirms that the sodium ion storage mechanism presents a capacity control response that is favorable to the fast kinetics of sodium. This indicates that it originates from the adsorption effect of abundant cavities and active sites.
[0130] Fig.10 (c) is a graph illustrating the ratio of the capacity contribution (capacitive contribution) to the total capacity based on the scan rate, which can be quantitatively evaluated by the following [Formula 2].
[0131] [Formula 2]
[0132] I(V)=k 1v +k 2v 1 / 2
[0133] Where I(V) is the overall current at a fixed potential (V), k 1v and k 2v 1 / 2 The diffusion and capacity contribution in the overall Na-ion storage capacity, respectively.
[0134] like Fig.10 As shown in (c), it can be confirmed that when the scan rate gradually increases from 0.1mV / s to 1mV / s, the capacity contribution ratio also gradually increases from 81.5% to 90.2%, and when the scan rate is 0.7mV / s, the capacity contribution ratio to the total is 87.5%.
[0135] Fig.10 (d) is a graph illustrating the relationship between the cyclic voltammetry (CV) curve and the capacity contribution at a scan rate of 0.7 mV / s. Fig.10 (d) shows that the capacity of the nitrogen-doped carbon is 87.5% of the total capacity at a scan rate of 0.7 mV / s, which confirms that the sodium ion storage capacity of the nitrogen-doped carbon is mostly derived from the fast capacitive response.
[0136] The high-capacity sodium ion storage mechanism described above can achieve a higher initial coulombic efficiency by reducing the role of sodium ions in the solid dielectric interphase (SEI) film formation reaction, which is consistent with the charge and discharge characteristic curves. In addition, the higher capacity contribution can also increase the speed of sodium ion batteries.
[0137] Output characteristics analysis
[0138] Fig.11 (a) is a graph illustrating the speed performance based on current density. When the current density gradually increases to 1, 2, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100 A / g, the reversible capacity will change to 265, 243, 221, 202, 178, 162, 150, 139, 122, 115, 108 and 102 mAh / g. The reversible capacity is 102 mAh / g when the current density is 100 A / g.
[0139] Re-read Fig.11 (a) shows that after cycling at 100 A / g, when the current density is reduced to 1 A / g, the reversible capacity is fully restored. The above results indicate that the non-intrinsic defects induced by nitrogen doping can show high capacity contribution, which is because sodium ions can move quickly with the help of medium-large hierarchical pore structure.
[0140] Fig.11 (b) is a graph comparing the speed performance between existing nitrogen-doped carbon and nitrogen-doped carbon nanoparticles applicable to the present invention, and compares and illustrates the reversible capacity based on current density of commercially available random nitrogen-doped carbon (Ref.20, Ref.42, Ref.44, Ref.41, Ref.43, Ref.31) and nitrogen-doped carbon nanoparticles applicable to the present invention.
[0141] See also Fig.11 (b) shows that the existing nitrogen-doped carbon can only increase the current density to 40 mA / g at most, while the present invention can provide sufficient reversible capacity even if the current density is increased to 100 mA / g, so its speed performance is very excellent.
[0142] See especially Fig.11(b), the nitrogen doping ratios of the existing nitrogen-doped carbons are 19.3at%, 17.72at%, 8.8at%, 9.89at%, 11.21at% and 7.78at%, respectively, while the nitrogen doping ratio of the nitrogen-doped carbon nanoparticles applicable to the present invention is 2.6at%, which confirms that although the nitrogen doping amount of the present invention is relatively small compared to the existing nitrogen-doped carbon, its speed performance is better. For reference, at% represents the composition ratio expressed in terms of atomic number, and the at% of the doped nitrogen will be calculated as (the number of nitrogen atoms / the number of atoms of the nitrogen-doped carbon nanoparticles)×100.
[0143] Fig.11 (c) is a graph illustrating the cycle performance at a current density of 100 mAh / g, which confirms that a reversible capacity of about 105 mAh / g can be provided in 5,000 cycles at a current density of 100 A / g. This indicates that a fast diffusion path for sodium ions can be achieved with the help of the high capacity contribution provided by the active sites and the nanostructuring of nitrogen-doped carbon nanoparticles.
[0144] As described above, the present invention relates to a method for manufacturing a nitrogen-carbon aggregate having a layered pore structure, a nitrogen-carbon aggregate manufactured using the above-mentioned manufacturing method, and a sodium ion battery containing the above-mentioned nitrogen-carbon aggregate, characterized in that: after a precursor solution containing a nitrogen-containing carbon precursor is manufactured, a pair of metal wires are arranged in the precursor solution, and then a power source is loaded to the metal wires for plasma discharge so that nitrogen is combined with the carbon of the carbon precursor to form nitrogen-doped carbon nanoparticles with a mixed-layer structure having micropores, and at the same time, an aggregate with a medium-large layered pore structure is formed by the agglomeration of carbon nanoparticles, thereby increasing the active sites of the aggregate by nitrogen doping.
[0145] As described above, the present invention can shorten the diffusion path of sodium ions by nanostructuring nitrogen-doped carbon nanoparticles and form voids by means of an internal mixed-layer structure, and can increase active sites by means of non-intrinsic defects formed by nitrogen doping and provide sufficient contact force for the cross-section between the electrode and the electrolyte, thereby making the movement of sodium ions easier and thereby easily achieving internal diffusion.
[0146] Therefore, the present invention can synthesize a nitrogen-carbon aggregate having macropores, mesopores and micropores and a mixed layer structure, and increasing active sites by means of non-intrinsic defects formed by nitrogen doping, thereby achieving improved conductivity and excellent discharge capacity, and can therefore be actually used as a cathode active material for sodium ion batteries.
[0147] The above contents are only exemplary descriptions of the technical ideas of the present invention, and persons with general knowledge in the technical field to which the present invention belongs can make various modifications and deformations without departing from the essential characteristics of the present invention. Therefore, the embodiments disclosed in the present invention are only used to illustrate the technical ideas of the present invention rather than to limit them, and the scope of the technical ideas of the present invention is not limited by the above embodiments. The protection scope of the present invention shall be interpreted according to the claims, and all technical ideas within the equivalent scope shall be interpreted as being included in the scope of the claims of the present invention.
Claims
1. A method for producing a nitrogen-carbon aggregate having a layered pore structure, characterized in that: include: In the first step, a precursor solution containing a nitrogen-containing carbon precursor is prepared; Step 2, placing a pair of metal wires into the precursor solution; as well as, The third step is to perform plasma discharge by applying power to the metal wire, so that the carbon of the carbon precursor is combined with nitrogen to form nitrogen-doped carbon nanoparticles having a mixed layer structure with micropores on the surface, and to form an aggregate having a medium-large layered pore structure through the aggregation of the carbon nanoparticles; The mixed layer structure of the nitrogen-doped carbon nanoparticles is composed of multiple crystalline regions. The nitrogen doping described above generates non-intrinsic defects that do not form a lattice in the crystalline region, thereby forming 10 to 20 The size of the space increases the active sites of the above-mentioned aggregate.
2. The method for producing a nitrogen-carbon aggregate according to claim 1, characterized in that: The nitrogen-containing carbon precursor, It is a heterocyclic amine with a nitrogen atom.
3. The method for producing a nitrogen-carbon aggregate according to claim 2, characterized in that: The above heterocyclic amines, The compound is at least one selected from the group consisting of pyridine, quinoline, isoquinoline, pyrrole, pyrrolidine, piperidine, indole, imidazole, pyrimidine and melamine.
4. The method for producing a nitrogen-carbon aggregate according to claim 1, characterized in that: The carbon nanoparticles, Its Brunauer-Emmett-Teller specific surface area is 200 to 400 m 2 / g.
5. A nitrogen-carbon aggregate, characterized in that: The method is manufactured by the manufacturing method according to any one of claims 1 to 4.
6. A sodium ion battery, characterized in that: include: An electrode comprising the nitrogen-carbon assembly according to claim 5; as well as, The electrolyte accommodates the above electrodes and uses sodium ions as a transfer medium.
Citation Information
Patent Citations
Sodium ion secondary battery
KR101635850B1
A nitrogen-doped porous carbon negative electrode energy storage material with long cycle performance and a preparation method thereof
CN109037680A